CONF. INT. ENSINO MATEMÁTICA 2008 - Braumann, Carlos (2009)
Conference organized by Direcção-Geral de Inovação e Desenvolvimento Curricular on the teaching of Mathematics, with conferences by international experts, discussion pannels, posters by techers and with a large participation of teachers of Mathematics. Held in Lisboa, Portugal, May 7-8, 2008.